AN ECONOMICS ANALYSIS OF OPERATIONAL PERFORMANCE AND GROWTH OF MILK FEDERATION IN KARNATAKA - Srinivasa .K .R; Netravathi; Revanasiddappa K. B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study aims to analyze the performance and growth of milk federation in Karnataka state. Karnataka Cooperative Milk Producers’ Federation Limited (KMF) is the apex body for the dairy co-operative movement in Karnataka. It is the second largest dairy co-operative amongst the dairy cooperatives in the country. In South India it stands first in terms of procurement as well as sales. One of the core functions of the Federation is marketing of Milk and Milk Products. The Brand ‘Nandini’ is the household name for pure and fresh milk and milk products. In Karnataka, as of 2023, there were 14 district milk unions covering all the districts of the state with 17550 dairy co-operatives registered, out of which, 15453 primary dairy co-operative societies are functioning under 16 district milk unions with an enrolment of 26 lakh milk producers under DCSs. The study focuses and majorly three objectives are - to study the historical background and performance of KMF in Karnataka, to evaluate the trends in growth and functioning of milk federation in Karnataka, and to analyze the DCSs, memberships, and milk production of KMF in the state.